Analisis Kemampuan Pemecahan Masalah dan Resiliensi Matematis Siswa ditinjau dari Gaya Kognitif Field Dependent dan Field Independent - Rana Rasyidah; Ririn Widiyasari (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research is motivated by the characteristics of receiving and processing different information for each student. These characteristics are usually called cognitive style. The main focus in this research is field dependent and field independent cognitive styles. The aim of this research is to describe mathematical problem solving abilities in terms of field dependent and field independent cognitive styles, describe students' mathematical resilience in terms of field dependent and field independent cognitive styles, and to determine the relationship between problem solving abilities and mathematic resilience in terms of field dependent and field independent cognitive styles. field independent. This research is research with a qualitative approach with a descriptive type. Data collection was carried out using GEFT test instruments, mathematical problem solving ability tests, interviews and mathematical resilience questionnaires. The data validation technique used is Triangulation technique. This research was conducted at SMPN 17 South Tangerang with research subjects in class VIII-10 totaling 6 students with 3 students with field dependent cognitive style and 3 students with field independent cognitive style. Based on the research results, it's find that the FD subjects, namely KMD, ZAF, and MAS, isn't able to fullfil the mathematical resilience indicators and isn't able to solve mathematical problems, while the FI subjects, namely DH, ABR, and JR is able to fullfil the mathematical resilience indicators and is able to solve mathematical problems.